(untitled) (Olhar de Professor, 2020)
Exploration is one of the usual forms of pedagogical activity in the kindergarten. In this paper, the idea of exploration is deepened, from a sensitive approach to space, objects, body and relationships. To explore is to ask, to ask oneself with the gesture and the senses, to question the object. In turn, we differentiate between the concepts of floor and ground, flat ceiling and frieze ceiling. Some assumptions are also reviewed from an interdisciplinary point of view (between psychomotricity and pedagogy) and images and metaphors are proposed to think about this way of approaching the experience of babies in the maternal, giving to explore.